Plankton Community Dynamics in the Pasur River Estuary: Correlations with Physicochemical Parameters, Nutrients, and Chlorophyll-a (The Dhaka University Journal of Earth and Environmental Sciences, 2026)
This investigation is centered on plankton communities in relation to physicochemical parameters, chlorophyll-a, and nutrients in the Pasur River Estuary, a crucial aquatic resource hub on the southwestern coast of Bangladesh. Water temperature was consistent throughout the stations, while salinity (4.86–5.08 ppt) and pH (6.67–6.92) values fluctuated slightly. Turbidity was high (211–265 NTU), and the DO value ranged between 3.3 mg L⁻¹ and 4.7 mg L⁻¹. The nutrient dynamics (ammonium: 22.94 µg/L, silicate: 218.25 µg/L, and phosphate: 7.64 µg/L) exhibited higher levels toward the river mouth and decreased seaward, except for phosphate. Chlorophyll-a (mean 5.13 µg/L) was largely controlled by nutrient dynamics, particularly ammonium concentration. Pearson correlation analysis was employed to examine the interrelationships among physicochemical variables, nutrients, chlorophyll-a, and plankton assemblages, revealing complex ecological linkages that regulate community structure and abundance. Coscinodiscus sp. and Metridia sp. were the most dominant among phytoplankton and zooplankton, respectively. The structural composition and density are attributed to the physicochemical and nutrient parameters from the perspective of spatial fluctuations. As this study was based on a single-season dataset, the findings represent a preliminary yet valuable baseline for understanding plankton–environment interactions in the Pasur River Estuary. The research provides essential baseline data for fisheries and bioresource management and emphasizes the need for multi-seasonal, long-term monitoring and ecosystem modeling to better capture the estuarine dynamics.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 14(2), 2025, P 177-191